(untitled) (Kronika Bydgoska, 2013)
The horse racing track in Bydgoszcz was established in Kapuściska Małe, at that time a village near the city, as one of the first in the Polish land, most probably in the years 1880-1882, and it was open until the year 1916. It was venue for gambling horse racing organised by the Bydgoszcz German horse racing society. When Bydgoszcz had found itself in the revived Polish state, nobody was interested in the track. Only in 1926, the Wielkopolska Horse Racing Society, failing to reach an agreement with the municipality in Poznań, proposed the city office in Bydgoszcz organisation of horse racing on the track in Kapuściska Małe. After organisation of the track, construction of sweepstake box offices and restaurant rooms, and renovation of the stands, the opening competition was held on October 10, 1926. The horse races were organised each year until 1931 in spring and autumn sessions, which usually lasted a dozen or so days. At that time, several so-called horse racing days were organised, with 7 or 8 horse races. Players had a chance to bet on one horse, triples and orders, with bets amounting to 10 złotys and multiples of this sum. Prizes for horse race winners reached even several thousand złotys. Horses from highly valued Polish stables of, e.g., Kazimierz Żychliński, count Ignacy Mielżyński, baron Leopold Kronenberg and count von Donnosmarck participated in the Bydgoszcz horse races, and riders included Olympians such as Karol Rómmel, Adam Królikiewicz, and Henryk Hubal-Dobrzański. In 1932, due to a crisis, the Bydgoszcz horse races were suspended. In the 1950s, the track was liquidated, and transformed into allotments.